PROBLEMATIQUE DE LA MISE EN ŒUVRE DE LA LEGISLATION SUR LE TRAVAIL DES ENFANTS DANS LA VILLE DE KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Lucien Nongo Loshima (IJRDO - Journal of Social Science and Humanities Research, 2019)
Although the law forbids the implication of the children in dangerous or unsanitary works, on the other hand, in the city of Kisangani in the Democratic Republic of Congo, the children participate in the exploitation of quarry stones. Yet, it is about a practice proscribed by the international right and by the Congolese legislation. In the sites of quarry stones in the city of Kisangani, the children deliver themselves to hard labors and that, during whole days. In counterpart, they are remunerated to currency of monkey. The Congolese state that is supposed to guarantee the respect of the legal instruments carrying protection of the child in similar circumstances seems to shine excessively by a laxity. From then on, he/it clearly appears that the children are abandoned to their sad fate and run serious risks so much for their health that for their future. Why are the children used in the dangerous works prohibited by the texts of right? What is the part of responsibility of the state in the perpetuation of such a practice? What are the risks run by the children who are used in the sector of quarry stones in the city of Kisangani? How to succeed in suppressing this practice and to succeed in warning long-term the use of the children in the careers of quarry stones in Kisangani?